Revitalizing CPAP adherence: lessons from THN study in patients with hypoglossal nerve stimulators - Mwenge, Gimbada Benny; Bousata, Jamila; Rodenstein, Daniel (Frontiers in Sleep, 2024)
This retrospective study aimed to address acceptance and long-term adherence to Continuous Positive Airway Pressure (CPAP) treatment among non-responder patients to ImThera THN system who initially declined this therapy.We employed a structured outpatient approach to communicate THN study results, categorize initial CPAP nonadherence reasons, and encourage CPAP trials through tailored appointments. Recorded follow-ups addressed individual concerns, providing medical guidance and acknowledging person-specific challenges. Adherence data were collected using CPAP hour meters at predetermined intervals, following Belgium's social security stipulations.Between July 2014 and October 2016, eleven participants, including one woman, with prior CPAP experience (average 2 months) were enrolled. Initial non-adherence was linked to ENT or psychological factors. Ten patients agreed to CPAP trials, where interventions included changing CPAP brand, pressure adjustments, mask changes, and additional measures like cognitive-behavioral therapy and nasal spray. After one year, mean adherence was 6.3 ± 2 hours/day, and average CPAP usage duration was 8.67 ± 2.13 years. As of November 2023, eight out of eleven patients were still actively using CPAPIn this investigation, we challenged the concept of CPAP non-adherence, highlighting evolving adherence and the significance of continuous monitoring and personalized interventions. Our findings underscore ongoing patient education, multidisciplinary support, and dynamic intervention adaptation for enhanced adherence in challenging patient populations. The results provide insights applicable to non-adherent patients with obstructive sleep apnea, emphasizing the importance of individualized care and sustained engagement for improved CPAP acceptance.